ALWIN - Algorithmic Chemical Notation System for Organic Compounds. Part II: Monocycles. (Non-conventional Methods in Document Retrieval. 17) - Sankar, P. V.; Krishnamurthy, E. V. (Journal of Information and Knowledge, 1972)
In part I of this series (1) we discussed the new chemical notation ALWIN for cyclic structures. This paper deals with the construction of ALWIN for monocyclic organic compounds such as benzene and other carbo-hetero monocycles (2).